Sistem Informasi Manajemen Aset Berbasis Web Di Badan Kesbangpol Ende Kabupaten Ende - Oktaviana Ina Palang; Ferdinandus Lidang Witi; Benediktus Yoseph Bhae (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2025)
The development of web-based information systems has become a primary need in supporting the efficiency and transparency of organizations, including government agencies. One of the agencies that requires innovation in asset management is the National Unity and Politics Agency (Kesbangpol) of Ende Regency. The assets owned by the Kesbangpol Agency need to be managed properly so that their use can be optimal and recorded accurately. Currently, the asset monitoring and evaluation (monev) system at the Ende Kesbangpol Agency is still carried out manually, which causes various obstacles, such as lack of data accuracy, difficulty in monitoring asset conditions, and slow evaluation processes. This has an impact on the effectiveness of asset management and can result in waste of resources. An information system or commonly abbreviated as SI is a system that combines human activities and the use of technology, which functions to collect, store, manage and disseminate information that is relevant to an organization. Currently, cloud-based information systems allow for the storage and processing of large amounts of population data that is measurable and cost-effective. Cloud systems allow remote access to information from anywhere with an internet connection. Assets are everything owned by a company that has economic value and can be used to generate income or profit in the future.